Does Fibrin Sealant Reduce Seroma after Immediate Breast Reconstruction Utilizing a Latissimus Dorsi Myocutaneous Flap? - Cha, Han Gyu; Kang, Sang Gue; Shin, Ho Seong; Kang, Moon Seok; Nam, Seung Min (Archives of Plastic Surgery, 2012)
Background The most common complication of latissimus dorsi myocutaneous flap in breast reconstruction is seroma formation in the back. Many clinical studies have shown that fibrin sealant reduces seroma formation. We investigated any statistically significant differences in postoperative drainage and seroma formation when utilizing the fibrin sealant on the site of the latissimus dorsi myocutaneous flap harvested for immediate breast reconstruction after skin-sparing partial mastectomy.Methods A total of 46 patients underwent immediate breast reconstruction utilizing a latissimus dorsi myocutaneous island flap. Of those, 23 patients underwent the procedure without fibrin sealant and the other 23 were administered the fibrin sealant. All flaps were elevated with manual dissection by the same surgeon and were analyzed to evaluate the potential benefits of the fibrin sealant. The correlation analysis and Mann-Whitney U test were used for analyzing the drainage volume according to age, weight of the breast specimen, and body mass index.Results Although not statistically significant, the cumulative drainage fluid volume was higher in the control group until postoperative day 2 (530.1 mL compared to 502.3 mL), but the fibrin sealant group showed more drainage beginning on postoperative day 3. The donor site comparisons showed the fibrin sealant group had more drainage beginning on postoperative day 3 and the drain was removed 1 day earlier in the control group.Conclusions The use of fibrin sealant resulted in no reduction of seroma formation. Because the benefits of the fibrin sealant are not clear, the use of fibrin sealant must be fully discussed with patients before its use as a part of informed consent.
Keywords: Seroma; Fibrin tissue adhesive; Mastectomy